PENCAPAIAN PERTUMBUHAN PADA BALITA GIZI BURUK SELAMA MENGIKUTI PEMULIHAN DI KLINIK GIZI BOGOR - Sri Muljati; Sihadi Sihadi; Amelia Amelia; Salimar Salimar; Rika Rahmawati (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 2006)
Growth Attainment of Severe Wasted Children Under Five Years Old Attending Out Patient Nutrition Clinic In Bogor.Background: Growth failure among children under five years old is widely known to cause high prevalence of severe malnutrition in Indonesia (3%). Treatment of those suffering from severe wasted children is done in out patient clinic in Bogor for six mounth period.Objective: To study growth attainment of severe wasting children and its related factors.Methods: A total of 536 children attending the clinic from 2001-2005 was selected according to inclusion criteria, some variables related to growth was also collected. They were divided into two groups who attained or not based on growth trajectory and analyzed by using Cox regessing model.Result: 20% children suffering from severe wasting attained growth after 6 months of treatment, while the rest failed. Growth attainment varied among children. Children aged less than 6 months, suffering less frequent influenza and having sign and symptom of severe malnutrition is was likely to attain growth based on growth trajectory.Recommendltlon: A more intensive care of severe wasted children is needed, which includes increasing compliance of food supplement consumption and improving awarenees of sign and symptoms of severe malnutrition.Keywords: growth trajectory, severe wasting